FT-IR and H-NMR characterization of the products of an ethylene inverse diffusion flame (2006)
ABSTRACT: Knowledge of the chemical structure of young soot and its precursors is very useful in the understanding of the paths leading to soot particle inception. This paper presents analyses of the chemical functional groups, based on FT-IR and 1H NMR spectroscopy of the products obtained in an ethylene inverse diffusion flame. The trends in the data indicate that the soluble fraction of the soot becomes progressively more aromatic and less aliphatic as the height above the burner increases. Results from 1H NMR spectra of the chloroform-soluble soot samples taken at different heights above the burner corroborate the infrared results based on proton chemical shifts (Ha, Hα, Hβ, and Hγ ). The results indicate that the aliphatic β and γ hydrogens suffered the most drastic reduction, while the aromatic character increased considerably with height, particularly in the first half of the flame. © 2006 The Combustion Institute. Published by Elsevier Inc. All rights reserved.